Mapping Doggerland : the Mesolithic landscapes of the Southern North Sea - Gaffney, Vincent L.,; Thomson, Kenneth, 1966-2007,; Fitch, Simon, (Archaeopress, 2007)
12,000 years ago the area that now forms the southern North Sea was dry land: a vast plain populated by Mesolithic hunter-gatherers. By 5500 BC the entire area had disappeared beneath the sea as a consequence of rising sea levels. Until now, this unique landscape remained hidden from view and almost entirely unknown. The North Sea Palaeolandscape Project, funded by the Aggregates Levy Sustainability Fund, have mapped 23,000 km2 of this 'lost world' using seismic data collected for mineral exploration. 'Mapping Doggerland' demonstrates that the North Sea covers one of the largest and best preserved prehistoric landscapes in Europe.